Characterizing the impact of sustained sulfadoxine/pyrimethamine use upon the Plasmodium falciparum population in Malawi. (December 2016) - Ravenhall, Matt; Benavente, Ernest; Mipando, Mwapatsa; Jensen, Anja; Sutherland, Colin; Roper, Cally; Sepúlveda, Nuno; Kwiatkowski, Dominic; Montgomery, Jacqui; Phiri, Kamija; Terlouw, Anja; Craig, Alister; et al.
Abstract Background Malawi experienced prolonged use of sulfadoxine/pyrimethamine (SP) as the front-line anti-malarial drug, with early replacement of chloroquine and delayed introduction of artemisinin-based combination therapy. Extended use of SP, and its continued application in pregnancy is impacting the genomic variation of thePlasmodium falciparum population. Methods Whole genome sequence data ofP. falciparum isolates covering 2 years of transmission within Malawi, alongside global datasets, were used. More than 745, 000 SNPs were identified, and differences in allele frequencies between countries assessed, as well as genetic regions under positive selection determined. Results Positive selection signals were identified withindhps, dhfr andgch1, all components of the parasite folate pathway associated with SP resistance. Sitting predominantly on adhfr triple mutation background, a novel copy number increase of twofold was identified in thegch1 promoter. This copy number was almost fixed (96.8% frequency) in Malawi samples, but found at less than 45% frequency in other African populations, and distinct from a whole gene duplication previously reported in Southeast Asian parasites. Conclusions SP resistance selection pressures have been retained in the Malawian population, with known resistancedhfr mutations at fixation, complemented by a novelgch1 promoter duplication. The effects of the duplication on the fitness costs of SP variants and resistance need to be elucidated.